PERKEMBANGAN TEKNOLOGI PENDIDIKAN DALAM PEMBELAJARAN PONDOK PESANTREN - Nia Syam Nuri (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2021)
This study aims to determine the effect of technological literacy on the quality of learning in SD Pondok Pesantren Lentera Hati. This research is a quantitative research with an ex post facto approach. The population of this study were all 22 elementary school teachers at the Lentera Hati Islamic Boarding School who were also used as research samples. Observations, documentation, and questionnaires were conducted for data collection. The data analysis technique used partial and multiple regression analysis. The results showed that there was a positive and significant influence between technological literacy on the quality of learning in SD Pondok Pesantren Lentera Hati. This can be seen from the correlation value of rx1y coefficient of 0.723 and coefficient of determination r2x1y value of 31.1%, so that the higher the technology literacy, the higher the quality of learning.